Defects in NADPH oxidase genes NOX1 and DUOX2 in very early onset inflammatory bowel disease - Hayes, P; Dhillon, S; O'Neill, K; Thoeni, C; Hui, K; Elkadri, A; Guo, C; Kovacic, L; Aviello, G; Alvarez, L; Griffiths, A; Snapper, S; et al. (Elsevier, 2015)
BACKGROUND and AIMS: Defects in intestinal innate defense systems predispose patients to inflammatory bowel disease (IBD). Reactive oxygen species (ROS) generated by nicotinamide-adenine dinucleotide phosphate (NADPH) oxidases in the mucosal barrier maintain gut homeostasis and defend against pathogenic attack. We hypothesized that molecular genetic defects in intestinal NADPH oxidases might be present in children with IBD. METHODS: After targeted exome sequencing of epithelial NADPH oxidases NOX1 and DUOX2 on 209 children with very early onset inflammatory bowel disease (VEOIBD), the identified mutations were validated using Sanger Sequencing. A structural analysis of NOX1 and DUOX2 variants was performed by homology in silico modeling. The functional characterization included ROS generation in model cell lines and in in vivo transduced murine crypts, protein expression, intracellular localization, and cell-based infection studies with the enteric pathogens Campylobacter jejuni and enteropathogenic Escherichia coli. RESULTS: We identified missense mutations in NOX1 (c.988G>A, p.Pro330Ser; c.967G>A, p.Asp360Asn) and DUOX2 (c.4474G>A, p.Arg1211Cys; c.3631C>T, p.Arg1492Cys) in 5 of 209 VEOIBD patients. The NOX1 p.Asp360Asn variant was replicated in a male Ashkenazi Jewish ulcerative colitis cohort. All NOX1 and DUOX2 variants showed reduced ROS production compared with wild-type enzymes. Despite appropriate cellular localization and comparable pathogen-stimulated translocation of altered oxidases, cells harboring NOX1 or DUOX2 variants had defective host resistance to infection with C. jejuni. CONCLUSIONS: This study identifies the first inactivating missense variants in NOX1 and DUOX2 associated with VEOIBD. Defective ROS production from intestinal epithelial cells constitutes a risk factor for developing VEOIBD.